ChemInform Abstract: Direct C—H Alkylation of Naphthoquinones with Amino Acids Through a Revisited Kochi—Anderson Radical Decarboxylation: Trends in Reactivity and Applications. Issue 14 (20th March 2013) - Naturale, Guillaume; Lamblin, Marc; Commandeur, Claude; Felpin, Francois‐Xavier; Dessolin, Jean
Abstract Highly functionalized naphthoquinones are prepared by Kochi—Anderson radical decarboxylation of amino acids.